Order preferencing and market quality on NASDAQ before and after decimalization - Chung, Kee H; Chuwonganant, Chairat; McCormick, D.Timothy (Journal of Financial Economics, 2004)
Despite the widely held belief that order preferencing affects market quality, no hard evidence exists on the extent and determinants of order preferencing and its impact on dealer competition and execution quality. This study shows that the bid-ask spread (dealer quote aggressiveness) is positively (negatively) related to the proportion of internalized volume during both the pre- and post-decimalization periods. Although decimal pricing led to lower order preferencing on NASDAQ, the extent of order preferencing after decimalization is higher than what prior studies had predicted. The price impact of preferenced trades is smaller than that of unpreferenced trades and preferenced trades receive greater (smaller) size (price) improvements than unpreferenced trades.